In Vivo Characterization of Endogenous Cardiovascular Extracellular Vesicles in Larval and Adult Zebrafish. Issue 9 (15th July 2021) - Scott, Aaron; Sueiro Ballesteros, Lorena; Bradshaw, Marston; Tsuji, Chisato; Power, Ann; Lorriman, James; Love, John; Paul, Danielle; Herman, Andrew; Emanueli, Costanza; Richardson, Rebecca J.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Extracellular vesicles (EVs) facilitate molecular transport across extracellular space, allowing local and systemic signaling during homeostasis and in disease. Extensive studies have described functional roles for EV populations, including during cardiovascular disease, but the in vivo characterization of endogenously produced EVs is still in its infancy. Because of their genetic tractability and live imaging amenability, zebrafish represent an ideal but under-used model to investigate endogenous EVs. We aimed to establish a transgenic zebrafish model to allow the in vivo identification, tracking, and extraction of endogenous EVs produced by different cell types. Approach and Results: Using a membrane-tethered fluorophore reporter system, we show that EVs can be fluorescently labeled in larval and adult zebrafish and demonstrate that multiple cell types including endothelial cells and cardiomyocytes actively produce EVs in vivo. Cell-type specific EVs can be tracked by high spatiotemporal resolution light-sheet live imaging and modified flow cytometry methods allow these EVs to be further evaluated. Additionally, cryo electron microscopy reveals the full morphological diversity of larval and adult EVs. Importantly, we demonstrate the utility of this model by showing that different cell types exchange EVs in the adult heart and that ischemic injury models dynamically alter EV production. Conclusions: We describe a powerful in vivo zebrafish model for the investigation of endogenous EVs in all aspects of cardiovascular biology and pathology. A cell membrane fluorophore labeling approach allows cell-type specific tracing of EV origin without bias toward the expression of individual protein markers and will allow detailed future examination of their function.